Factors associated with the development of diabetes mellitus in older caregivers - Ana Carolina Ottaviani; Estefani Serafim Rossetti; Mariélli Terassi; Allan Gustavo Brigola; Bruna Moretti Luchesi; Érica Nestor Souza; Nathalia Alves de Oliveira; Keika Inouye; Sofia Cristina Iost Pavarini; Fabiana de Souza Orlandi
ABSTRACT Objective: evaluate the factors associated with the risk of diabetes mellitus in older caregivers. Method: this is a cross-sectional study conducted with 326 older caregivers enrolled in Family Health Units. Data were collected using a sociodemographic characterization questionnaire, clinical and care information, and the Finnish Diabetes Risk Score to assess the risk of developing diabetes. Results: 35.5% of the caregivers presented a high risk of developing diabetes. The factors associated with the risk of developing diabetes were: use of medication (OR = 3.88), satisfactory or poor health assessment (OR = 1.72), and the fact of being female (OR = 0.48). Conclusion: more than one third of older caregivers present high risk of developing diabetes. Therefore, being female, living with other people, using medication, and having a poor health assessment are factors associated with increased risk of developing diabetes.